INCIDENCE OF STUNTING AND ITS RELATIONSHIP WITH FOOD INTAKE, INFECTIOUS DISEASES, AND ECONOMIC STATUS IN KENDARI, SOUTHEAST SULAWESI, INDONESIA - Akhmad, Akhmad; Yadi, Sahmad; Farma, Ikhwana (YCAB Publisher & IAKMI SULTRA, 2016)
Background: Stunting is characterized by inhibition of growth in children that lead to failure in getting normal heights and healthy child's age. It is a public health problem in the working area of Public Health Center of Mata, Kelurahan Mangga Dua in Kendari in 2016.Objective: This study aims to examine the relationship between food intake, infectious diseases, economic status and the incidence of stunting in Kendari, Southeast Sulawesi, IndonesiaMethods: This was a descriptive cross sectional study with retrospective approach. This research was conducted in Public Health Center of Mata. There were 41 respondents were selected as the samples. Data were collected by questionnaires, observation, and documentation. Data were analyzed using Chi-Square test. Results: The results showed that there were significant associations between food intake (p= 0.001), infectious diseases (p= 0.000), economic status (p= 0.000), and the incidence of stunting in infants.Conclusions: It can be concluded that there is a relationship between food intake, infectious diseases and economic status with the incidence of stunting in children aged 2-4 years in the working area of Public Health Center of Mata, Kendari. Therefore, good food intake is needed for the growth and development of the child. Moreover, changing the behavior of parents by doing the healthy and clean behavior in the household to prevent infectious diseases in children infectious diseases is also very important. Economic status however also plays key role in the incidence of stunting in children.